2009
DOI: 10.1253/circj.cj-08-0591
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Electrical Remodeling of L- and T-Type Ca2+ Channels in Rat Right Atrium With Monocrotaline-Induced Pulmonary Hypertension

Abstract: t is well known that fibrillating or hemodynamically overloaded atria are subject to cellular electrical remodeling, which is characterized by shortening of the action potential 1 and often contributes to the occurrence and persistence of atrial fibrillation (AF). AF and chronic obstructive pulmonary disease (COPD) frequently coexist and complicate treatment of both clinical conditions. 2,3 COPD patients are susceptible to secondary pulmonary hypertension (PH), and the resulting hemodynamic changes, and in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It has been reported by Santana et al 35 that ouabain can activate I Ca(TTX) and might contribute to the ouabain-induced increase in the cardiac [Ca 2+ ] i transient. Of note, Koyama et al 45 also showed the reappearance of I Ca,T in the presence of 10μmol/L TTX in rat atrial myocytes after monocrotaline-induced pulmonary hypertrophy. However, it is peculiar that the recorded I Ca,T current was insensitive to 100μmol/L NiCl 2 which eliminates the possibility that the recorded current was indeed I Ca,T .…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported by Santana et al 35 that ouabain can activate I Ca(TTX) and might contribute to the ouabain-induced increase in the cardiac [Ca 2+ ] i transient. Of note, Koyama et al 45 also showed the reappearance of I Ca,T in the presence of 10μmol/L TTX in rat atrial myocytes after monocrotaline-induced pulmonary hypertrophy. However, it is peculiar that the recorded I Ca,T current was insensitive to 100μmol/L NiCl 2 which eliminates the possibility that the recorded current was indeed I Ca,T .…”
Section: Discussionmentioning
confidence: 93%
“…Although AF is frequently recognized as a marker of postcapillary PH or clinical group 2 PH [19], we found that PH hemodynamic phenotype was not independently associated with incident AF. The pathophysiology of atrial arrhythmias in PH has been linked to right atrial fibrosis [20] as a result of chronic hypoxia and structural remodeling from chronic right atrial pressure overload [21], stretching [16], and remodeling with electrophysiological alterations in calcium channels [22]. Specifically, isthmus-dependent or typical atrial flutter has been described as a potentially separate entity in patients with PH given that right-sided cardiac chambers are implicated in its pathophysiology [6].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effects of PAH-induced remodelling on atrial electrical activity, we identified relative changes in atrial remodelling from experimental data in MCT-induced PAH rats [18,[25][26][27][28], dogs [20,29], rabbits [11] and humans [7][8][9][30][31][32][33][34][35][36][37][38][39]. These experimental data encompass changes in the expression of ion channel-related genes, Ca 2+ -handling-related genes, connexin genes, fibrosis-related genes and inflammasome-related genes [9,[12][13][14][15]18,19,40] (figure 1a).…”
Section: Methodsmentioning
confidence: 99%
“…Prolonged APD/ERP has been consistently observed in the RA of animals and humans [7][8][9]18,[25][26][27][28][30][31][32][33][34][35][36][37][38][39]. The prolonged APD can be attributed to PAH-induced remodelling of atrial potassium (K + ) currents, including reductions in Kcnj2, Kcna5 and Kcnq1.…”
Section: Mechanism Of Pah-induced Af Due To Ap Prolongation In the Ramentioning
confidence: 99%